Upaya Pelestarian Lingkungan Melalui Penguatan Ekologi Keluarga Berbasis Al-Quran - Ina Salmah Febriani (Pusat Studi Gender dan Anak (PSGA) Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Sultan Maulana Hasanuddin Banten, 2022)
Pollution and environmental damage are an unavoidable phenomenon nowadays. The Forum for the Environment (WALHI) noted that the earth's temperature is currently increasing by 1.1 degrees Celsius, carbon dioxide emissions are also increasing, forests are decreasing due to the large number of mining areas and oil palm plantations. According to the 2018 Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES), Indonesia continues to lose 650 thousand hectares of forest every year. The National Disaster Management Agency (BNPB) also noted that throughout 2020 there were 2925 disasters in Indonesia, including floods, landslides, cyclones, forest fires. Apart from these thousands of disasters, one important thing that is no less damaging is the awareness to reduce the use of plastic. Plastics that are still used in everyday life because of materials that are not derived from biological compounds. Plastic has properties that are difficult to degrade (non-biodegradable). Plastic is estimated to take 100 to 500 years to completely decompose. Plastic bag waste can pollute the soil, water, sea, and even the air. This paper will describe how family ecology plays an important role in environmental preservation based on the Koran.